Existentialism - Philosophy Of Life - Normatova Dildor Esonalievna (Genius Journals, 2024)
In this article, it is philosophically revealed that existentialism is called human life, philosophy of living and philosophy of tension, and the main thing that existentialists study is the meaning of a certain human life. The essence of existentialism, which gained new and special importance in the first half of the 20th century, was scientifically analyzed.
Keywords: Existentialism; social consciousness; existence